Morphological and ecological data confirm Reithrodontomys cherrii as a distinct species from Reithrodontomys mexicanus - Martínez-Borrego, Daily; Arellano, Elizabeth; Cruz, Daryl D.; González-Cózatl, Francisco X.; Nava-García, Elizabeth; Rogers, Duke S. (THERYA, 2021)
The integrative taxonomy approach has recently been widely suggested in systematic studies. Lines of evidence such as the geometric morphometrics and ecological analyses have been useful for discriminating between genetically well-differentiated species. Within the genus Reithrodontomys, R. mexicanus is one of the more taxonomically complex species, being considered a cryptic species complex. R. cherrii was considered a subspecies of R. mexicanus, until molecular evidence raised it to the species-level. Herein, we evaluate these two forms using morphological and ecological data based on the premise that they constitute genetically differentiated species. We carried out geometric morphometric analyses on dorsal and ventral views of the skull. Landmark and semi-landmark configurations for both views of the skull were selected based on previous studies of cricetid rodents. We tested the presence of sexual dimorphism, and the skull shape and size differences between species on both cranial views. Additionally, we characterized the environmental space of each species habitat using bioclimatic variables, elevation, and the Normalized Difference Vegetation Index (NDVI). Females and males of R. mexicanus and R. cherrii did not show sexual dimorphism in shape or size of both skull views. We found significant differences between the two species in both shape and size of the skull. Cranial structures of the ventral view were more useful to differentiate both species. R. mexicanus exhibited a broader environmental space than R. cherrii, with relatively similar values of temperature and elevation, but not of precipitation. The pairwise comparison showed significant differences in the majority of the environmental variables analyzed. Although for each view, we found statistical differences in the skull shape of R. cherrii and R. mexicanus, the ventral side showed major resolutive power differentiating both species. Our findings suggest that R. cherrii tends to have a larger skull than R. mexicanus. However, the morphological and pelage coloration similarity between these species reported in the past, could explain the previous inclusion of R. cherrii as a subspecies of R. mexicanus. R. mexicanus occurs in a variety of vegetation-types coinciding with the broader environmental space that it occupies compared to that of R. cherrii. The natural areas where both species are distributed were associated with high NDVI values. Our results complement the molecular evidence and, under an integrative taxonomy approach, support R. cherrii as a different species from R. mexicanus.